PENGARUH MEDIA FLASH CARD TERHADAP PERKEMBANGAN BAHASA ANAK KELOMPOK B DI TK NURUS SA’ADAH 03 KECAMATAN LEDOKOMBO KABUPATEN JEMBER - I Made Hartawan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2018)
Teachers can carry out their duties and responsibilities well if they can deliver students until the learning objectives that have been assigned these roles require teachers to have the ability and skills in the learning process such as mastery of teaching methods, learning strategies, communicating. One method that is expected to improve the ability of children in developing the language is the use of Flash cards or picture cards. Subjects in this study were students of group B TK Nurus Sa'adah 03 District Ledokombo Jember District. The method used is purposive sampling. Which respondents function through the method of observation. In analyzing this data, as free variable is playing Falsh card, while the dependent variable is language development. Thus it can be seen that the working hypothesis received is the Influence of Flash Card Media on Language Development of children B TK Nurus Sa'adah 03 District Ledokombo Jember District. From the results of the researchers at the time of data collection, that the phenomenon in detail can be well understood.